Safety‐II—Resilience in the face of abnormal operation. Issue 2 (16th November 2020) - Cutchen, Steven S.
Abstract: Traditional process safety, Safety‐I, is the condition where adverse outcomes are minimized, for example, OSHA PSM. Adverse Outcomes result from unusual (erroneous) actions in usual conditions. Safety‐I applies to situations that were planned. While process safety incident rates have improved dramatically under Safety‐I, industry seems to have reached an asymptote. There is a Safety‐I gap for unplanned situations, those with no procedures, the initiating event type for a majority of incidents. Work‐as‐Done does not align with Work‐as‐Imagined. Operational Discipline defined in terms of following procedures cannot apply. Safety‐II, the condition where adaption and recovery to safe conditions are maximized, applies where Safety‐I is weak. Adverse Outcomes result from usual (normal) actions in unusual conditions, when workers do what appears to make sense at the time, but the situation is not as expected. Safety‐I and Safety‐II processes are both vital. S ystem improvement results from Safety‐I. S ystem robustness results from Safety‐II. Safety‐II provides for Resilience . Safety‐II is not formally implemented in the United States. This article introduces the concepts behind Safety‐II, the justification for adoption of Safety‐II to cover unplanned operation, and an outline for beginning implementation.